1990
DOI: 10.1111/j.1365-2249.1990.tb03321.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activity during measles

Abstract: SUMMARYNatural killer cells are postulated to play an important role in host anti-viral defences. We measured natural killer cell activity in 30 individuals with acute measles (73 + 21 lytic units (LU)/10' cells) and 16 individuals with other infectious diseases (149 + 95 LU) and found it reduced compared with values for adults (375 + 70 LU; P<000\) or children (300±73 LU, P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…*p < 0.05. (Okada et al, 2000) and that loss of NK cell activity is correlated with measles disease progression (Griffin et al, 1990). Taken together, these previous results imply that NK cells play an important role in protection against both certain viral infections and progression of these viral diseases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…*p < 0.05. (Okada et al, 2000) and that loss of NK cell activity is correlated with measles disease progression (Griffin et al, 1990). Taken together, these previous results imply that NK cells play an important role in protection against both certain viral infections and progression of these viral diseases.…”
Section: Discussionmentioning
confidence: 91%
“…Numerous studies have found that human NK cells are important in the immune response to a number of viruses, including influenza virus, vaccinia virus, hepatitis B virus, WNV, HIV-1, and measles virus (Griffin et al, 1990;Johansson et al, 2011;Kottilil et al, 2003;Lin et al, 2012;Shabani et al, 2014;Vidal et al, 2011;Zhang et al, 2010). Additionally, NK cell activation levels are negatively correlated with virus DNA levels in infected patients (Kottilil et al, 2003;Shabani et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…However, MV has been shown to depress IL-12 synthesis in vitro and to dampen NK cell activity in vivo (Griffin et al, 1990b;Karp et al, 1996). Production of IL-12 from DCs is also suppressed by MV (Karp et al, 1998).…”
Section: Suppression Of Il-12mentioning
confidence: 99%
“…With regard to other innate defence mechanisms, MV does not appear to hamper either complement activation in vitro or IFN-γ production in vivo (Patrick Sissons et al, 1979). However, MV has been shown to depress IL-12 synthesis in vitro and to dampen NK cell activity in vivo (Griffin et al, 1990b;Karp et al, 1996). In addition to their antiviral function, IFN-α/β have potent effects in regulating specific immune response.…”
Section: Modulation Of T Cell Responsementioning
confidence: 99%
“…MeV replication in vitro is sensitive to the inhibitory effects of IFNα/β. There is little evidence that type I IFN is produced in vivo during the acute phase of disease (Griffin et al, 1990; Leopardi et al, 1992; Schnorr et al, 1993; Tanabe et al, 2003; Yu et al, 2008) and this may be important for virulence as mutation of the V gene leads to virus attenuation (Devaux et al, 2011). IL-1 and IL-8 can be detected in plasma (Zilliox et al, 2007), but roles for these factors in control of MeV infection have not been identified.…”
Section: Immune Response and Clearancementioning
confidence: 99%